Heart Rate and Blood Pressure Response to Short-Term Head-Down Bed Rest: A Nonlinear Approach - Balocchi, R.; Di Garbo, A.; Michelassi, C.; Chillemi, S.; Varanini, M.; Barbi, M.; Legramante, J. M.; Raimondi, G.; Zbilut, J. P. (Methods of Information in Medicine, 2000)
Although it is well-known that prolonged exposure to microgravity environment such as in space travel results in derangements of orthostasis, recent evidence suggests that even short-term exposure may have similar effects and parallels such common examples as prolonged bed rest. Whereas spectral analysis of heart rate and systolic blood pressure have been unable to detect changes, we hypothesized that nonlinear indexes may be better able to uncover such perturbations. Eighteen healthy subjects were exposed to 4-hour head-down tilt, and of these, 4 exhibited fainting. Two nonlinear indexes, mutual information and recurrence quantification were used to analyze the data. Only recurrence quantification was able to detect a “decoupling” of heart rate and systolic blood pressure at rest using discriminant analysis (p < 0.05). These results suggest that orthostatic intolerance may be due to a decoupling of heart rate from systolic blood pressure reflexive activity occurring at rest.
Keywords: Orthostasis; Microgravity; Mutual Information; Recurrence Quantification